Clonagem e expressão em Pichia pastoris da forma truncada da glicoproteína D (gD) de Herpesvírus Bovino tipo 5 - Dummer, Luana Alves (2008)
Outbreaks of fatal meningoencephalitis caused by Bovine Herpesvirus type 5 (BoHV-5) cause important economic losses in national trade of bovine beef. Commercial vaccines developed against Bovine Herpesvirus type 1 can protect cattle of neurological disease caused by BoHV-5. These cross-reactions are due to its genetic and antigenic similarities of both BoHV-1 and 5. However, these vaccines can not prevent latent infection of BoHV-5, even viral spread to healthy animals. This way, new vaccines strategies are based on envelope glycoproteins and are focusing safety, economic viability and on prevention of BoHV-5 latency and spread. This glycoprotein acts in initial steps of viral infection and glycoprotein D has drawn the attention in studies carried out with BoHV-1 and other homologous herpesvirus. The gD acts on viral membrane fusion with permissive cells through glycoproteins and host receptors interactions, so it is essential for viral entry. A vaccine that is capable to stimulate specific humoral and cellular immunity against BoHV-5 must be developed. The aim of this work was the production of a recombinant truncated form of gD of BoHV-5 in yeast Pichia pastoris and its antigenicity and immunogenicity evaluation. Data show that yeast P. pastoris can express the truncated form of BoHV-5 gD to the supernatant due to its secretion of ~190mg/L of recombinant protein, simplifying protein purification. The recombinant protein was successfully recognized by antibodies of animals immunized with BoHV-5, suggesting its antigenicity and immunogenicity and that native protein characteristic are conserved. The data presented herein allow the design of future studies aiming at expression optimization and further immunogenicity evaluation, as well as its capacity to neutralize the virus in biological models and on cattle.